Applying IFRS 9 to Central Banks Foreign Reserves - World Bank (World Bank, Washington, DC, 2016)
Effective January 1, 2018, IFRS 9 Financial Instruments will replace IAS 39 Financial Instruments: Recognition and Measurement (IAS 39). Unlike most publications on IFRS 9, this paper focuses primarily on the application of the new standard on central banks’ foreign reserve assets, which increasingly constitute a substantial part of central banks’ balance sheet. Based on IFRS 9 implementation assessment projects with several central banks, the World Bank RAMP accounting team identified six factors that can help central banks determine appropriate business model for foreign reserve assets. Empirically, the result of applying the six factors has indicated that central banks’ reserve portfolios often display elements of more than one business model; hence management judgment coupled with a well-articulated accounting policy paper will be critical when implementing IFRS 9. Under most central banks reserves management frameworks, performing the solely payments of principal and interest (SPPI) test should be a relatively straightforward exercise, and the practical expedient option under the new impairment provisions should also apply.